Sensitivity of MR Diffusion Measurements to Variations in Intracellular Structure: Effects of Nuclear Size - Xu, Junzhong (2009)
Magnetic resonance imaging measurements of the apparent rate of water diffusion in tumors are sensitive to variations in tissue cellularity, which have been shown useful for characterizing tumors and their responses to treatments. However, because of technical limitations on most MRI systems, conventional pulse gradient spin echo (PGSE) methods measure relatively long time scales, during which water molecules may encounter diffusion barriers at multiple spatial scales, including those much greater than typical cell dimensions. As such they cannot distinguish changes on sub-cellular scales from gross changes in cell density. Oscillating gradient spin echo (OGSE) methods have the potential to distinguish effects on restriction at much shorter time and length scales. Both PGSE and OGSE methods have been studied numerically by simulating diffusion in a three-dimensional, multi-compartment tissue model. The results show that conventional measurements with the PGSE method cannot selectively probe variations over short length scales and, therefore, are relatively insensitive to intracellular structure, whereas results using OGSE methods at moderate gradient frequencies are affected by variations in cell nuclear sizes and can distinguish tissues that differ only over sub-cellular length scales. This additional sensitivity suggests that OGSE imaging may have significant advantages over conventional PGSE methods for characterizing tumors.